Selective review and commentary on emerging pharmacotherapies for opioid addiction - Miotto K; Torrington M; Nielsen S; Zhao M; Mooney L; Ling W (Dove Medical Press, 2011)
Walter Ling1, Larissa Mooney1, Min Zhao2, Suzanne Nielsen1, Matthew Torrington1, Karen Miotto1 1Integrated Substance Abuse Programs, University of California, Los Angeles, CA, USA; 2Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, China Abstract: Pharmacotherapies for opioid addiction under active development in the US include lofexidine (primarily for managing withdrawal symptoms) and Probuphine®, a distinctive mode of delivering buprenorphine for six months, thus relieving patients, clinicians, and regulatory personnel from most concerns about diversion, misuse, and unintended exposure in children. In addition, two recently approved formulations of previously proven medications are in early phases of implementation. The sublingual film form of buprenorphine + naloxone (Suboxone®) provides a less divertible, more quickly administered, more child-proof version than the buprenorphine + naloxone sublingual tablet. The injectable depot form of naltrexone (Vivitrol®) ensures consistent opioid receptor blockade for one month between administrations, removing concerns about medication compliance. The clinical implications of these developments have attracted increasing attention from clinicians and policymakers in the US and around the world, especially given that human immunodeficiency virus/acquired immunodeficiency syndrome and other infectious diseases are recognized as companions to opioid addiction, commanding more efforts to reduce opioid addiction. While research and practice improvement efforts continue, reluctance to adopt new medications and procedures can be expected, especially considerations in the regulatory process and in the course of implementation. Best practices and improved outcomes will ultimately emerge from continued development efforts that reflect input from many quarters. Keywords: buprenorphine, naltrexone, probuphine, lofexidine, implant buprenorphine, buprenorphine film